Anatomy of the Holocene inundation of an isolated carbonate platform: Bermuda North Lagoon, western Atlantic. (30th July 2018) - Gischler, Eberhard; Kuhn, Gerhard
Abstract: The detailed Holocene inundation history of the Bermuda North Lagoon may be used as model for transgressive and highstand sequences in carbonate platforms. Sedimentation and facies development were controlled largely by sea‐level rise and antecedent topography. Four late Pleistocene to Holocene sequences may be identified in North Lagoon based on a combined analysis of 200 km shallow reflection seismics and 39 cores including 29 radiometric and U/Th‐ages. The sequences were deposited during sea‐level highstands and are separated by subaerial exposure horizons that formed during sea‐level lowstands. Sequence 1 (inferred MIS 7) consists of well‐cemented carbonate sands. Sequence 2 (MIS 5) is up to 20 m thick and consists of well‐sorted, inter‐reefal sands and reef sediments with mound‐like structures. Sequence 3 (inferred MIS 3) is up to ca 6 m thick and accumulated in topographic lows of the underlying sequences some 20 m below modern sea‐level. Sequence 4 (MIS 1, Holocene) includes lagoonal sediments up to 10 m thick, and reefs that accumulated on topographic highs of the MIS 5 sequences. Holocene sediments in topographic lows include peat, peaty sediment, freshwater mud, restricted marine carbonates, and open lagoonal carbonate sediments deposited in seagrass beds, shallow water, and deeper lagoon areas. Upward fining is an expression of deepening and the development of a reef‐protected lagoon environment. Holocene sedimentation on topographic highs usually lacks freshwater and transitional facies and starts with shallow marine mollusc shell accumulations overlain by carbonate sediments that show fining upward. Packstone (68%), wackestone (22%), grainstone (9%) and mudstone (1%) textures occur in cores, with Halimeda, molluscs, coralline algae and foraminifera being the most common constituent particles; coral fragments are rare. During the Holocene, an estimated volume of 1 km 3 of carbonate sediments was deposited in North Lagoon. Average sedimentation rates are estimated to be 0.32 m/kyr. Abstract : Four late Quaternary sequences may be identified on the Bermuda carbonate platform based on a combined analysis of 200 km shallow reflection seismics and 39 cores including 29 radiometric and U/Th‐ages. The sequences were deposited during late Pleistocene and Holocene sea‐level highstands and are separated by subaerial exposure horizons that formed during sea‐level lowstands. The detailed Holocene inundation history of this modern carbonate platform may be used as model for transgressive sequences in such environments in the fossil record.